Overexpression, clinical significance and potential mechanisms of protein kinase D1 in hepatocellular carcinoma: multi-omic analyses and pharmacological insights - Zhen-dong Chen; Hui-ping Lu; Yan-ting Zhan; Fei-yan He; Liang-qin Zhu; Yu-long Deng; Xi-ni Wei; Min-ying Yang; Kai Qin; Yu-xing Tang; Ke-jun Wu; Zhi-guang Huang; et al. (Functional & Integrative Genomics, 2026)

NaOH-induced dual-vacancy engineering in ZnCdS solid solutions for enhanced photocatalytic hydrogen evolution - Rong Yan; Chunyan Du; Danlian Huang; Lin Shi; Hanbo Yu; Wenbo Xu; Yu Yang; Tian Ao; Tong Sun; Shasha Yi; Jingyi Jiang; Yiyi Deng (Journal of Environmental Chemical Engineering, 2026)

A dual-function electroactive hydrogel platform for mitigating oxidative stress and restoring muscle function - Yi Lin; Zi-Hao Lin; Hai-Bin Jiang; Yu-Hao Kang; Qing-Song Deng; Rong-Tai Zuo; Zhi-Qi Lin; Er-Peng Yang; Jun-Jie Xu; Clara Chen; Xi-Ming Wang; Jin-Zhong Zhao (Chemical Engineering Journal, 2026)

Discovery and engineering of a compost-derived thermophilic BHETase for enhanced depolymerization of post-consumer PET - Xiaoli Zhou; Xian Li; Yi Zang; Lian Zhou; Guangda Feng; Ming-Rong Deng; Honghui Zhu (Journal of Hazardous Materials, 2026)

Reaction-generated secondary phase advances electronic-phonon decoupling and boosted mechanical performance in Bi0.42Sb1.58Te3 alloys - Yi-lin Liu; Hao Liang; Chong-Yu Wang; Jiang-Hu Yu; Kang Yue; Qian Deng; Ju Rong; Jing Feng; Zhen-Hua Ge (Chemical Engineering Journal, 2026)

Environmental Factors Drive Neurodegenerative Diseases Through Glutamate Excitotoxicity: A Convergent Mechanistic Pathway - Yulu He; Tingting Yi; Meixin Min; Ke Xu; Huan Lin; Rong Xu; Dan Deng; Xiaoping Xiao (Neuroscience Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Methionine-driven covalent chelation of Zn2+ by linusorb: a paradigm in hydrophobic cyclic peptide metal binding - Yi-kang Zhang; Du-jian Deng; Zhong-yi Luo; Wan-nan Wang; Jun-le Li; Shao-rong Zhang; Jia-li Li; Jia-zi Chen; Yong Wang; Zi-zhe Cai (Food Chemistry, 2026)

Buffering failure of the ratio of secondary to primary phases: Risk overestimation of soil heavy metals under alkaline conditions - Yingdong Wu; Zixin Zeng; Rong Teng; Junwei Yang; Jiang Yu; Hui Sun; Siwei Deng; Pengxinyue Huang; Jie Luo; Yi Wu; Xuetao Zhao (Journal of Hazardous Materials, 2026)

School greenspace and myopia incidence and burden in Chinese children and adolescents: The Guangzhou children and adolescents cohort study - Xiao-Qi Zhu; Yi Sun; Rong Lin; Ya-Na Luo; Jia-Xin Li; Yi-Dan Zhang; Michael S. Bloom; Matthew H.E.M. Browning; Sam SS. Lau; Shu-Jun Fan; Zhi-Qi Li; Ming-Deng Xiang; et al. (Environmental Research, 2026)

Investigating the Therapeutic Efficacy of Quality-Controlled, miR-146a-5p-Enriched Small Extracellular Vesicles Derived From MSCs Against Idiopathic Pulmonary Fibrosis - Xin Wang; Lingjiao Meng; Qiuhong Wang; Ruixue Rong; Yu Zhang; Xiaohui Zhao; Chen Liang; Huizhen Guo; Li Deng; Zengqi Tan; Feng Guan; Yi Tan (Stem Cell Reviews and Reports, 2026)
Small extracellular vesicles derived from umbilical cord mesenchymal stem cells (UC-sEvs) may be used for the treatment of idiopathic pulmonary fibrosis (IPF) because of their ability to control inflammation and inhibit fibrosis. However, the lack of clarity regarding the treatment mechanism of IPF and the corresponding quality standards limit the clinical application of these small extracellular vesicles. Here, we established a good manufacturing practice (GMP) grade process for isolating UC-sEvs, and RNA-seq was performed to screen for potential therapeutic cargo in the product to confirm the therapeutic effect of nebulized UC-sEv agents against IPF. Functionally, UC-sEvs inhibited the pulmonary inflammatory response by regulating macrophage function, thereby suppressing the bleomycin toxicity-induced progression of fibrosis. Mechanistically, miR-146a-5p enrichment in UC-sEvs may be involved in alleviating bleomycin-induced IPF by targeting TRAF6/IRAK1 to negatively regulate inflammation. The proposed quality control strategy ensures the stability of the product across three batches, with RNA-seq analysis revealing highly similar miRNA expression profiles. The feasibility of using miR-146a-5p as a key therapeutic molecule has been validated. Finally, on the basis of the results of pharmacodynamics and key therapeutic molecule studies, we provided a detailed quality control standard for IPF therapy by nebulizing UC-sEv. These findings help understand how sEvs impact IPF and the possible consequences of their therapeutic usage and offer a quality standard reference. Graphical Abstract

Corrigendum to “Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells” [Vet. Microbiol. 310 (2025) 110723] - Kui Xu; Yu-Ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

Microbial community assembly driven by dissolved organic matter and sulfate induces arsenic transformation in shallow aquifers of lateritic red soil regions - Ming-Zhu Chen; Jun-Feng Wang; Jian-Ping Ouyang; Yi-Rong Deng; Mei-Ting Yang; Yu-Dian Xun; Xiao-Hui Shi; Guang-Yong Tang; Jian-Ying Mo; Han-Jie Ye; Qu-Sheng Li (Journal of Hazardous Materials, 2025)

The crucial role of immune factors in susceptibility to SARS-CoV-2 infection and severity of COVID-19 - Xing-Hao Yu; Rong-Rong Cao; Yi-Qun Yang; Han-Wen Cao; Fei-Yan Deng; Shu-Feng Lei (Molecular Genetics and Genomics, 2025)

Research on Acoustic-Electrical Integrated Technology in Geothermal Resource Exploration, Development and Monitoring - Feng Chu; Rui Xu; Rong-hua Zhang; Yi-guo Xue; Deng-rui Wu; Lin-zhi Lang; Shu-ge Liu; Jing-kai Qu (Applied Geophysics, 2025)

Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells - Kui Xu; Yu-ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

A new framework integrating crop growth–level IV fugacity model and eco-indicator sensitivity to assess neonicotinoid fate and ecological risk in tropical rice–vegetable rotations - Huadong Tan; Xinyu Hu; Linxia Zhang; Yiru Chen; Rong Hao; Zhenzhen Wang; Chunyuan Wu; Xiaoying Zhang; Xiao Deng; Yi Li; Lin Wu; Yi Zhang (Journal of Hazardous Materials, 2025)

The application of manure and straw is beneficial for improving the content and stability of DOM in paddy soil - Qinghua Zhou; Jiayue Zhou; Weiliang Xiong; Shiwei Li; Ouping Deng; Yi Xiao; Xingyu Li; Bing Li; Changquan Wang; Xuesong Gao; Genchuan Bai; Jiang Liu; et al. (Journal of Environmental Management, 2025)

Codon usage bias analysis of self-incompatibility genes BrSRK, BrSLG, and BrSP11/BrSCR in Brassica rapa reveals insights into their coevolution - Yi-zhong Zhang; Min Ji; Lin-qiong Deng; Li-kun Lian; Li Jian; Rong-xian Zhang (Genetic Resources and Crop Evolution, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Impact of cyclolinopeptide (linusorb) on oxidative stability of hot-pressed flaxseed oil and their interaction with phospholipid - Jia-hui Yu; Shao-rong Zhang; Yue Du; Du-jian Deng; Yi-kang Zhang; Jun-le Li; Li-jun Hu; Wenyi Chen; Xin Yue; Yong Wang; Jiazi Chen; Zi-zhe Cai (Food Chemistry, 2025)

Glycoside hydrolase PgGal31A inhibits citrus blue mold via modifying cell wall components - Rong Zhu; Ou Chen; Yao Xu; Jian Huang; Huali Wang; Lili Deng; Shixiang Yao; Lanhua Yi; Kaifang Zeng (Postharvest Biology and Technology, 2025)

Substrate preference triggers metabolic patterns of indigenous microbiome during initial composting stages - Yi Ren; Chen Liu; Jiayu Luo; Xuhui Deng; Daoyue Zheng; Jiahui Shao; Zhihui Xu; Nan Zhang; Wu Xiong; Hongjun Liu; Rong Li; Youzhi Miao; et al. (Bioresource Technology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Design, synthesis and antifungal activity of novel pyrazole-amide-isothiazole derivatives as succinate dehydrogenase inhibitors - Ai-ling Bao; Xian-song Xie; De-yuan Wang; Zi-quan Deng; Yun Chen; Dan Liu; Wei-yi Li; Xiao-rong Tang; Wei Cheng; Ying-kun Yan (Food Chemistry, 2025)

Associations between volatile organic compounds exposure and multiple oxidative damage biomarkers: Method development, human exposure, and application for e-waste pollution prediction - Jia-Rong Wang; Hong-Xuan Kuang; Ye Liu; Xin-Yi Li; Tian-Hong Chen; Xiao-Hui Zhu; Rui-Fang Fan; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

Regional-scale biogeographical patterns of soil extracellular enzyme activities across eight Chinese fir plantation locations - Han-shuo Zhang; Mi-lin Deng; Hao Yang; Bi-jiang Fang; Wen-feng Lan; Qiu-hua Ma; Huai-feng Weng; Zhi-jie Yang; Yi-rong Zhang; Yong Zheng (European Journal of Soil Biology, 2024)

Graphene oxide quantum dots (GOQDs) induce behavioral disorders via the disturbance of kynurenine pathway in zebrafish larvae - Shun Deng; Enming Zhang; Yunyang Zhao; Hao Guo; Lan Luo; Song Yi; Bingxin Zheng; Xiaoyuan Mu; Kezhu Yuan; Xuangen Deng; Haibo Rong; Yanbo Ma; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Enhancing biohydrogen production from xylose through natural FeS2 ore: Mechanistic insights - Yun Xu; Miao-yu Deng; Si-jia Li; Yi-cheng Yuan; Hao-yu Sun; Quan Wang; Rong-ping Chen; Lei Yu (Bioresource Technology, 2024)

Composition of DOM along the depth gradients in the paddy field treated with crop straw for 10 years - Rong Huang; Zheng Li; Yi Xiao; Jiang Liu; Tao Jiang; Ouping Deng; Xiaoyang Tang; Yingjie Wu; Qi Tao; Qiquan Li; Youlin Luo; Xuesong Gao; et al. (Journal of Environmental Management, 2024)

Efficacy of pterostilbene suppression on Aspergillus flavus growth, aflatoxin B1 biosynthesis and potential mechanisms - Yong-Mei Hu; Yi-Rong Wang; Wen-Bin Zhao; Yan Yan Ding; Zheng-Rong Wu; Guang-Han Wang; Peng Deng; Shao-Yong Zhang; Jun-Xia An; Zhi-Jun Zhang; Xiong-Fei Luo; Ying-Qian Liu (International Journal of Food Microbiology, 2023)

Urban greenspace types influence the microbial community assembly and antibiotic resistome more in the phyllosphere than in the soil - Xin-Rong Huang; Roy Neilson; Le-Yang Yang; Jing-Jun Deng; Shu-Yi-Dan Zhou; Hu Li; Yong-Guan Zhu; Xiao-Ru Yang (Chemosphere, 2023)

Characterization of the fragmented mitochondrial genome of domestic pig louse Haematopinus suis (Insecta: Haematopinidae) from China - Rong Li; Yu Nie; Yi-Tian Fu; Yuan-Ping Deng; Wei Wang; Ping-Ping Ma; Guo-Hua Liu (Systematic Parasitology, 2023)

Effects of anti-pull ties on the bearing behaviors of shallow tunnel-type anchorages in soft rock - Ya-feng Han; Xin-rong Liu; Erdi Abi; Yi-liang Tu; Bin Xu; Xiao-han Zhou; Zhi-yun Deng; Zhong-hao Wang (Journal of Mountain Science, 2023)

The spatial distribution, health risk, and cytotoxicity of metal(loid)s in contaminated field soils: The role of Cd in human gastric cells damage - Jiao-Yang Ma; Wei-Yu Li; Zi-Yue Yang; Jin-Zhou Su; Li Li; Yi-Rong Deng; Yun-Fei Tuo; You-Ya Niu; Ping Xiang (Science of The Total Environment, 2023)

Short-Term Limited Water Irrigation Influences the Photosynthetic Pigments, Enzymatic and Non-Enzymatic Activities in Saccharum spontaneum L. at Vegetative Stage - Zhi-Nian Deng; Hai-Rong Huang; Cheng-Mei Huang; Krishan K. Verma; Hai-Bin Luo; Sheng-Li Jiang; Yi-Jie Li; Hui-Qing Cao; Kai-Chao Wu; Lin Xu (Sugar Tech, 2023)

Genetic Diversity Analysis of Sugarcane (Saccharum spp. hybrids) Among High-Sucrose Clones of GT Series and Commonly Used Parents by Using Microsatellite Markers in Guangxi, China - Hai-Rong Huang; Yi-Jing Gao; Mukesh Kumar Malviya; Krishan K. Verma; Manoj Kumar Solanki; Yu-Xin Huang; Xiang Li; Yuchi Deng; Jing Yan; Shi-Yun Tang; Lun-Wang Wang; Lin Xu (Sugar Tech, 2022)

Small RNA Sequencing Analysis of Germinating Single-bud Seedcane Sett in Sugarcane - Kai-Chao Wu; Lin Xu; Zhi-Nian Deng; Tian Pang; Rong-Hua Zhang; Yi-Jie Li; Xiao-Yan Liu; Cheng-Feng Huang; Wen-Xian Qin; Jian-Feng Wei; Li-Ping Wei; Yang-Rui Li; et al. (Sugar Tech, 2021)

Interferon-γ produced by tumor-infiltrating NK cells and CD4+ T cells downregulates TNFSF15 expression in vascular endothelial cells - Yi Lu; Xin Gu; Li Chen; Zhi Yao; Juan Song; Xiulong Niu; Rong Xiang; Tao Cheng; Zhihai Qin; Weimin Deng; Lu-Yuan Li (Angiogenesis, 2014)

The Influence of Plant Growth Regulators and Light Quality on Somatic Embryogenesis in China Rose (Rosa chinensis Jacq.) - Ji-Ren Chen; Lian Wu; Bo-Wen Hu; Xing Yi; Rong Liu; Zi-Niu Deng; Xing-Yao Xiong (Journal of Plant Growth Regulation, 2014)

Comments on ‘Influences of the Bermuda High and atmospheric moistening on changes in summer rainfall in the Atlanta, Georgia region, USA ’ - Wenhong Li; Laifang Li; Rong Fu; Yi Deng; Hui Wang (International Journal of Climatology, 2013)
In a recent article, Diem (2012) examined the impact of the North Atlantic Subtropical High ( NASH ) and atmospheric moistening on summer rainfall variability in the Atlanta, Georgia region. In his paper, he indicated that the results concerning the variability of the NASH western ridge discussed in Li et al . (2011) are incorrect. We present new evidence here to show that the comments by Diem (2012) are unjustified; the main conclusions in Li et al . (2011) were drawn according to the data over a 60‐year (1948–2007) and 45‐year (1958–2002) periods of NCEP / NCAR and ERA ‐40 reanalysis, whereas conclusions of Diem (2011) were based upon the trend analysis of a similar but different index of the NASH using sub‐periods of 1948–2009 (since late 1970s). The comment emphases the importance of climate dynamics to study precipitation variability over the Southeastern US and further strengthens the conclusions originally put forth in Li et al . (2011): over the last 60 years (1948–2007), the NASH has shown a significant trend of westward movement, and the meridional movement of the NASH western‐ridge (i.e. its latitudinal change) has enhanced in the recent three decades.

Protective effect of rat pancreatic progenitors cells expressing Pdx1 and nestin on islets survival and function in vitro and in vivo - Shu-yan Zhou; Yu-sen Zhang; Qing Li; Yi Zhang; Hui Qi; Han-xin Zhou; Chun-yan Deng; Fu-rong Li (Journal of Physiology and Biochemistry, 2012)

Cordyceps cicadae extracts ameliorate renal malfunction in a remnant kidney model - Rong Zhu; Yi-ping Chen; Yue-yi Deng; Rong Zheng; Yi-fei Zhong; Lin Wang; Lan-ping Du (Journal of Zhejiang University-SCIENCE B, 2011)

Promoter Analysis of Mouse Scn3a Gene and Regulation of the Promoter Activity by GC Box and CpG Methylation - Guang-Fei Deng; Jia-Ming Qin; Xun-Sha Sun; Zu-Ying Kuang; Tao Su; Qi-Hua Zhao; Yi-Wu Shi; Xiao-Rong Liu; Mei-Juan Yu; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Journal of Molecular Neuroscience, 2011)

Effect of SPLUNC1 protein on the Pseudomonas aeruginosa and Epstein-Barr virus - Hou-De Zhou; Xiao-Ling Li; Gui-Yuan Li; Ming Zhou; Hua-Ying Liu; Yi-Xing Yang; Tan Deng; Jian Ma; Shou-Rong Sheng (Molecular and Cellular Biochemistry, 2008)

Genetic linkage of human height is confirmed to 9q22 and Xq24 - Yao-Zhong Liu; Peng Xiao; Yan-fang Guo; Dong-Hai Xiong; Lan-Juan Zhao; Hui Shen; Yong-Jun Liu; Volodymyr Dvornyk; Ji-Rong Long; Hong-Yi Deng; Jin-Long Li; Robert R. Recker; et al. (Human Genetics, 2006)